Transcriptomic analysis of Pinellia ternata (Thunb.) Breit T2 plus line provides insights in host responses resist Pectobacterium carotovorum infection. Issue 1 (1st January 2021) - Shu, Fuxing; Han, Jing; Ndayambaje, Jean Pierre; Jia, Qi; Sarsaiya, Surendra; Jain, Archana; Huang, Minglei; Liu, Minghong; Chen, Jishuang
ABSTRACT: Transcriptome is used to determine the induction response of Pinellia ternata (Thunb.) Breit T2 plus line (abbreviated as PT2P line) infected with Pectobacterium carotovorum . The main objective of the study was to deal with the transcriptome database of PT2P line resistance to soft rot pathogens to provide a new perspective for identifying the resistance-related genes and understanding the molecular mechanism. Results indicated that water soaking and tissue collapse started at 20 h after PT2P line was infected by P. carotovorum . A total of 1360 and 5768 differentially expressed genes (DEGs) were identified at 0 h and 20 h, respectively. After 20 h of infection, growth and development-related pathways were inhibited. Meanwhile, DEGs were promoted the colonization of P. carotovorum pathogens in specific cell wall modification processes at the early infected stage. A shift to a defensive response was triggered at 0 h. A large number of DEGs were mainly up-controlled at 20 h and were substantially used in the pathogen recognition and the introduction of signal transformation cascades, secondary metabolites biosynthesis, pathogenic proteins activation, transcription aspects and numerous transporters. Furthermore, our data provided novel insights into the transcript reprogramming of PT2P line in response to P. carotovorum infestation. Graphical abstract: uf0001